Аналіз потенційних ризиків комплексної системи протидії інформаційним загрозам - Даниленко, М. С.; Соколюк, В. А.; Клушин, Д. Д.; Безрук, В. М. (ХНУРЕ, 2025)
The modern technological base provides a fairly wide range of software and hardware tools to counteract malicious influences that pose a potential threat to network infrastructure and data in file storage. However, based on the existing world experience in protecting against cyber threats, it can be stated that only a multi-level complex system can provide a significant level of security. On the other hand, any complex system has potential vulnerabilities that can be used by an attacker to successfully implement an attack. Therefore, to maintain network information security, it is necessary not only to deploy a protection system, but also to audit its possible vulnerabilities and localize each of them
Keywords: протидія інформаційним загрозам; інформаційна загроза